2013
DOI: 10.1038/icb.2013.98
|View full text |Cite
|
Sign up to set email alerts
|

Natural cytotoxicity receptors and their ligands

Abstract: Natural killer (NK) cells are innate lymphoid cells (ILCs) that participate to the clearance of pathogen-infected cells and tumour cells. NK cells and subsets of ILCs express the natural cytotoxicity receptors (NCRs) NKp46, NKp44 and NKp30 at their surface. NCRs have been shown to recognize a broad spectrum of ligands ranging from viral-, parasite- and bacterial-derived ligands to cellular ligands; however, the full identification of NCR ligands remains to be performed and will undoubtedly contribute to a bett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
234
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(237 citation statements)
references
References 99 publications
(155 reference statements)
1
234
0
2
Order By: Relevance
“…and the inhibitory receptor NKG2A (62)(63)(64). Results from our microassays indicated that the ChAT + NK cells had no increase of cytolytic activity, which was confirmed in vitro by a cytotoxic assay of YAC-1 cells (Fig.…”
Section: Ly6cmentioning
confidence: 57%
“…and the inhibitory receptor NKG2A (62)(63)(64). Results from our microassays indicated that the ChAT + NK cells had no increase of cytolytic activity, which was confirmed in vitro by a cytotoxic assay of YAC-1 cells (Fig.…”
Section: Ly6cmentioning
confidence: 57%
“…16-21 In spite of many efforts, so far, the panel of the NCR ligands has been only partially defined. 10,12,22 A reason of these difficulties is related to the fact that study models of receptor-ligand interaction for the NCR are rather limited, as only NKp46 is expressed also on NK cells of rat and mouse. Moreover, although the NCRs belong to the Ig superfamily, they greatly differ in their molecular structure, implying that their ligands may be rather heterogeneous.…”
Section: Introductionmentioning
confidence: 99%
“…Pattern recognition receptors, such as Toll-like receptors, c-type lectin, and natural cytotoxic receptors (NCRs), are germ line-encoded cell surface receptors that allow for spontaneous activation of effector cells of the innate immune system (23)(24)(25). FcγRs, in contrast, are responsible for bridging the innate and adaptive responses by providing an interface between innate immune cells and antigen-specific antibodies.…”
Section: Significancementioning
confidence: 99%